2011
DOI: 10.1002/jemt.20906
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of microcirculation and histomorphology of two different flap donor sites

Abstract: For the first time, significant differences in the in vivo microperfusion and histomorphology could be shown when comparing two different free-flap donor sites. The correlation to flap failure needs to be substantiated in further systematic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…IVCM is a new in vivo transcutaneous imaging method to study cutaneous microcirculation. It is non‐invasive and allows observing the capillary flow and imaging the tissue under observation, evaluating parameters like skin thickness, epidermal cell size, number of capillaries/mm 2 , size, shape, and depth of the microvessels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IVCM is a new in vivo transcutaneous imaging method to study cutaneous microcirculation. It is non‐invasive and allows observing the capillary flow and imaging the tissue under observation, evaluating parameters like skin thickness, epidermal cell size, number of capillaries/mm 2 , size, shape, and depth of the microvessels .…”
Section: Discussionmentioning
confidence: 99%
“…The German group of Altintas et al (2)(3)(4)(5)(6)(7)(8) has recently suggested evaluating skin microcirculation using in vivo reflectance confocal microscopy (IVCM), an emerging non-invasive skin imaging technique, with the advantage of associating quantitative data on blood flow with morphological data on the analyzed tissue. These authors measured the 'Quantitative blood cell flow' (QBCF) by counting blood cells passing through a given capillary recorded by IVCM.…”
mentioning
confidence: 99%